Economic development in Iran, 1900-1970 - Bharier, Julian (London ; New York : Oxford University Press, 1971)
This book is devoted to an analysis of the major determinants of the rate and level of Iran's economic development: human resources; economic growth and structures; fiscal and monetary policies; the role of government; capital and technology; foreign trade and payments; agriculture forestry and fishing; mining and the oil industry; manufacturing; transport and communication, and banking among others.
Map on lining paper.
Includes index.
Includes bibliographical references: p. 283-303.
lje 28/09/2018
Loans
Keywords: Economic development; Economic growth; Iran